The Real-World CONSEQUENT ALL COMERS Study: Predictors for Target Lesion Revascularization and Mortality in an Unselected Patient Population. (September 2021) - Langhoff, Ralf; Arjumand, Jawed; Waliszewski, Matthias; Reimer, Peter; Härtel, Dirk; Hohl, Christian; Raut, Werner; Romani, Sebastian; Alós, Jesús; Martínez, Esaú; Schmidt, Albrecht; Yahya, Shaiful Azmi; et al.
We evaluated the safety and efficacy of a resveratrol-paclitaxel-coated peripheral balloon catheter in an all-comer patient cohort undergoing endovascular treatment of above-the-knee and below-the-knee peripheral artery disease. CONSEQUENT ALL COMERS (Clinical Post-Market Clinical Follow-up [PMCF] on Peripheral Arteries treated with SeQuent Please OTW [Over-the Wire]) is a prospective, single-arm, multicenter observational study (ClinicalTrials Identifier: NCT02460042). The primary end point was the 12-month target lesion revascularization (TLR) rate. Secondary end points included vessel patency, target vessel revascularization, and all-cause mortality. A total of 879 lesions in 784 consecutive patients (71.3 ± 10.4 years old, 57.7% male) were analyzed; 53.3% had claudication, whereas the remaining 46.7% exhibited critical limb ischemia (CLI). Substantial comorbidities were present, including diabetes mellitus (41.2%), smoking (66.1%), and coronary artery disease (33.9%). Lesion length (879 lesions) was 12.0 ± 9.3 cm and 31.8% were Transatlantic Inter-Society Consensus II C/D lesions. The overall technical success rate of the 1269 drug-coated balloon (DCB)'s used was 99.6% (1.60 ± 0.79 DCB's/patient). At 12 months, the TLR rates were 6.3% in patients with CLI and 9.6% in claudicants, with a primary patency rate of 89.9% and 87.1%, respectively. All-cause mortality was 4.3% (28/658). The most important predictors for TLR were female gender, in-stent restenosis at baseline and lesion length.